2004
DOI: 10.1577/02-106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation, Temporal Stability, and the Absence of Isolation by Distance among Atlantic Herring Populations

Abstract: Abstract.-The genetic variation among 17 spawning groups of Atlantic herring Clupea harengus was assessed at several temporal and spatial scales using nine tetranucleotide microsatellites. PanAtlantic samples were drawn from the Scotian Shelf, the Celtic Sea, the Baltic Sea, and coastal Iceland. Significant differentiation was observed between northeastern and northwestern Atlantic herring (F ST ϳ 0.065) and among northwestern Atlantic spawning groups (max F ST ϭ 0.014) at the spatial scale of the Scotian Shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 35 publications
7
30
1
Order By: Relevance
“…homing behaviour) produce restricted gene flow between discrete spawning units. Such a synergistic impact of hydrographic and behavioural factors on the genetic structure of marine fish has previously been reported in cod (Ruzzante et al 2000) and Atlantic herring Clupea harengus (McPherson et al 2004).…”
Section: Complex Genetic Structure Patterns In the North Seasupporting
confidence: 61%
See 1 more Smart Citation
“…homing behaviour) produce restricted gene flow between discrete spawning units. Such a synergistic impact of hydrographic and behavioural factors on the genetic structure of marine fish has previously been reported in cod (Ruzzante et al 2000) and Atlantic herring Clupea harengus (McPherson et al 2004).…”
Section: Complex Genetic Structure Patterns In the North Seasupporting
confidence: 61%
“…In addition, the inter-annual stability of the genetic differentiation patterns observed in this study should be tested. Indeed, population genetics could become a useful tool for fisheries management, but only if temporally stable patterns of genetic structure can be established (Lundy et al 1999, McPherson et al 2004. Furthermore, more effort should be allocated to sampling in Atlantic waters, to obtain a more detailed description of whiting population structure.…”
Section: Perspectives For Future Managementmentioning
confidence: 99%
“…A sample of western Atlantic herring spawners from Nova Scotia, Canada (Trinity Ledge, as described in McPherson et al 2004) was also assayed and compared to North Sea data.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the application of highly variable microsatellite DNA markers has proven to be informative for detecting subtle genetic structuring in Atlantic herring in the western Atlantic (McPherson et al 2004) and sub-Arctic waters (Shaw et al 1999), but findings thus far have not identified putative underlying causes or the most applicable population model for the species. The elucidation of such aspects is central to our understanding of not only population connectivity in the sea, but also impacts on the utility of the stock concept in fisheries management.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the NE Atlantic populations, herring in the NW Atlantic undergo north-south and inshore-offshore migrations for feeding and reproduction (19), with spawning taking place mostly during spring and autumn (20) from Cape Cod to northern Newfoundland (14). Previous genetic studies based on a small number of microsatellite markers reported weak but significant genetic structuring between NW and NE Atlantic populations as well as among spawning aggregations within the NW Atlantic (21,22).…”
Section: Significancementioning
confidence: 99%